Hollywood moon : a novel - Wambaugh, Joseph (New York : Grand Central Pub., 2010)
There is saying at Hollywood station that the full moon brings out the beast, rather than the best, in the precinct's citizens. One moonlit night, LAPD veteran Dana Vaughn and "Hollywood" Nate Weiss, a struggling actor turned cop, get a call about a young man who's been attacking women. Meanwhile, two surfer cops known as Flotsam and Jetsam keep bumping into an odd, suspicious duo, a smooth talking player in dreadlocks and a crazy eyed, tattooed biker. No one suspects that all three dubious characters might be involved in something bigger, more high tech, and much more illegal. After a dizzying series of twists, turns, and chases, the cops will find they've stumbled upon a complex web of crime where even the criminals can't be sure who's conning whom. The author gets inside the hearts and minds of the cops whose jobs have them constantly on the brink of danger. By turns heart wrenching, exhilarating, and laugh out loud funny, this novel is his most thrilling and deeply affecting ride yet through the singular streets of Los Angeles.
Keywords: Police -- California -- Los Angeles -- Fiction; Hollywood (Los Angeles, Calif.) -- Fiction; Mystery fiction